VALIDation of the IBD-Disk Instrument for Assessing Disability in Inflammatory Bowel Diseases in a French Cohort: The VALIDate Study. (17th May 2020) - Le Berre, Catherine; Flamant, Mathurin; Bouguen, Guillaume; Siproudhis, Laurent; Dewitte, Marie; Dib, Nina; Cesbron-Metivier, Elodie; Goronflot, Thomas; Hanf, Matthieu; Gourraud, Pierre-Antoine; Kerdreux, Elise; Poinas, Alexandra; et al.
Abstract: Background and Aims: Inflammatory bowel diseases [IBD] are disabling disorders. The IBD-Disability Index [IBD-DI] was developed for quantifying disability in IBD patients but is difficult to use. The IBD-Disk is a visual adaptation of the IBD-DI. It has not been validated yet. The main objectives were to validate the IBD-Disk and to assess the clinical factors associated with a change in the score and its variability over time. Methods: From May 2018 to July 2019, IBD patients from three university-affiliated hospitals responded twice to both IBD-Disk and IBD-DI at 3–12 month intervals. Validation included concurrent validity, reproducibility, and internal consistency. Mean IBD-Disk scores were compared according to clinical factors. Variability was assessed by comparing scores between baseline and follow-up visits. Results: A total of 447 patients [71% Crohn's disease, 28% ulcerative colitis] were included in the analysis at baseline and 265 at follow-up. There was a good correlation between IBD-Disk and IBD-DI [r = 0.75, p <0.001]. Reproducibility was excellent [intra-class correlation coefficient = 0.90], as well as internal consistency [Cronbach's α = 0.89]. The IBD-Disk was not influenced by IBD type but was associated with female gender and physician global assessment. Extra-intestinal manifestations, history of resection, elevated C-reactive protein and faecal calprotectin also tended to be associated with higher disability. The IBD-Disk score decreased in patients becoming inactive over time. Conclusions: This study validated the IBD-Disk in a large cohort of IBD patients, demonstrating that it is a valid and reliable tool for quantifying disability for both CD and UC.